Pillar[6]arene‐based Molecular Trap with Unusual Conformation and Topology. Issue 11 (10th August 2018) - Tan, Li‐Li; Li, Yupeng; Jin, Yinghua; Zhang, Wei; Yang, Ying‐Wei
Abstract: A new low‐density pillar[6]arene‐based SOF (P6‐SOF‐2) with unusual topology of 3D uninodal 6‐connected pcu alpha‐Po primitive cubic topology for P6 was successfully constructed. In P6‐SOF‐2, each P6 ring adopts unprecedented C 2 symmetric chair‐like conformation. More importantly, P6‐SOF‐2 owned 3D interconnected channels and large void volume, which would facilitate gas molecule transportation and adsorption. Binding sites, binding energies and interactions of C2 H2, CO2 and C2 H4 were investigated via SCC‐DFTB calculations. These gases preferred to trap in unguiculate intrinsic cavity of P6, like a molecular trap. Governed by size‐exclusive effect and van der Waals interactions, the order of the binding of the adsorbed gases by P6‐SOF‐2 is CO2 >C2 H2 >C2 H4, which facilitates the possible selective adsorption properties. Our study opens new perspectives in the development of SOFs. Abstract :